Online Voting System Based on Blockchain - Prasanna, B.T; Rakshitha, R (International Journal of Computer Sciences and Engineering, 2021)
Voting plays an important role in making decision and is an serious event as it determines the fate of a nation. In Current voting System, voters cast their vote in an appointed polling stations, which usually involves more expenditure on time and cost budget. In this paper aiming to implement the application of Blockchain as a service to implement distributed Online Voting Systems. Blockchain based Online Voting System (BOVS) to enhance the integrity, optimize the voting process, produce consistent voting results, strengthen the transparency of the voting system and and it doesnot allow duplicate votes and is fully tamper proof. In this System voting is convenience to users as voters can vote from their devices without extra cost and effort. In this paper we explore the advantges of Online voting system based on Blockchain technology.